Intensive fishing has not forced dietary change in the South American fur seal (Arctophoca australis) off Río de la Plata and adjoining areas - Vales, Damián Gustavo (2013)
1. South American fur seals (Arctophoca australis) inhabiting the Río de la Plata plume and adjoining areas are known to forage upon a wide range of prey (i.e. pelagic, demersal and benthic species). 2. Since the 1960s, trawlers have operated in the area, targeting primarily demersal and benthic species. Carbon and nitrogen stable isotope ratios from 54 adult male fur seals dead stranded along the coast of southern Brazil from 1994 to 2011 were analysed to investigate whether the intensification of fishing in Río de la Plata and adjoining areas since the mid-1990s has reduced the availability of benthic and demersal prey to the growing population of South American fur seals. 3. No significant correlation between δ13C or δ15N values and stranding year was found, thus revealing that fur seals maintained a steady diet over 17 years. 4. Reconstruction of the isotopic landscape of the study area using potential prey of fur seals showed a spatial segregation, with prey from southern Brazil typically enriched in 13C and depleted in 15N compared with those from northern Argentina. Most adult male fur seals relied mainly on small pelagic fishes and squid captured on the continental shelf, whereas medium pelagic and demersal?benthic prey played a minor role in the diet. 5. It is concluded that South American fur seals rely on pelagic resources (i.e. small pelagic fish and squid) more strongly than previously thought and that their diet does not reflect the varying abundance of demersal?benthic resources in the area.